HUBUNGAN ANTARA PHYSICAL APPEARANCE PERFECTIONISM DAN BODY SATISFACTION PADA PENGGUNA TIKTOK - Gantari, Nadiyah Sadira; Nurmala, Nurmala; Masyhadi, Anisia Kumala (Psikologi UHAMKA, 2025)
TikTok, as a popular social media platform among teenagers and young adults, influences how individuals view and assess their physical appearance. Exposure to content that emphasizes lifestyle, fashion, and ideal body image can increase physical appearance perfectionism and affect Body satisfaction. This study aims to examine the relationship between physical appearance perfectionism and Body satisfaction in TikTok users. A quantitative approach with purposive sampling was used in this study, involving 139 participants (M = 18.08; SD = 3.01) aged 13-24 years. The instruments used were the Physical Appearance Perfectionism Scale (PAPS) and the Adolescent Body Image Satisfaction Scale (ABISS) which have been adapted into Indonesian. The results of the analysis showed a significant negative relationship between physical appearance perfectionism and Body satisfaction (r = -0.505, p < 0.01), which means that the higher the physical appearance perfectionism, the lower the Body satisfaction in TikTok users. Further research is recommended to explore different age groups or other social media platforms to expand the generalizability of the findings. Keywords: adolescents; Body satisfaction; physical appearance perfectionism; social media; tiktok